Understanding Abnormal Psychology / Basic Psychology - Frude Neil (Blackwell Publishers, 1998)
This book offers an animated and comprehensive introduction to common psychological problems, and guides beginning students in both psychology and clinical psychology through theoretical debates and practical therapies. Acknowledgements, Introduction, Anxiety Disorders, Eating Disorders, Affective Disorders, Schizophrenia, Drug Abuse, Sexual Dysfunction and Sexual Disorders, Organic Disorders, Learning Disability, References, Author and Subject Index.